Rancang Bangun Sistem Manajemen Administrasi Menggunakan Metode Waterfall Berbasis Web dan Android - Raul Nazil Ariono; Muhammad Imron Rosadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Al-Karomah Pandan Foundation still relies on manual administrative processes, which often lead to delays and data inaccuracies. This study aims to develop a web- and Android-based administrative management system to address these issues. The web system was developed using the Laravel framework with PHP and SQL as the database manager, while the Android system was built using the Flutter framework. The development methodology applied was Waterfall, as it is suitable for administrative systems with a clear workflow. Each stage was carried out in a structured manner to ensure that all requirements were met before proceeding to the next stage. System testing was conducted using the blackbox testing method to verify that all functions worked according to requirements, and the results showed that all main features could be used without errors. In addition, user satisfaction testing using the System Usability Scale (SUS) achieved an average score of 75.78%, which falls into the good category, particularly in features such as student attendance, teacher attendance, student re-registration, re-registration payments, tuition (SPP) payments, and exam payments. This study demonstrates that the implementation of an integrated digital system can improve administrative efficiency, data accuracy, and the overall quality of management in educational foundations.